The German CaRe high registry for familial hypercholesterolemia: Sex differences, treatment strategies, and target value attainment - März, Winfried; Schmidt, Nina; an Haack, Ira; Dressel, Alexander; Grammer, Tanja B.; Kleber, Marcus E.; Baessler, Andrea; Beil, F. Ulrich; Gouni-Berthold, Ioanna; Julius, Ulrich; Kassner, Ursula; Katzmann, Julius L.; et al. (Atherosclerosis plus, 2023)
Background and aims - Familial hypercholesterolemia (FH) is among the most common genetic disorders in primary care. However, only 15% or less of patients are diagnosed, and few achieve the goals for low-density lipoprotein cholesterol (LDL-C). In this analysis of the German Cascade Screening and Registry for High Cholesterol (CaRe High), we examined the status of lipid management, treatment strategies, and LDL-C goal attainment according to the ESC/EAS dyslipidemia guidelines. - Methods - We evaluated consolidated datasets from 1501 FH patients diagnosed clinically and seen either by lipid specialists or general practitioners and internists. We conducted a questionnaire survey of both the recruiting physicians and patients. - Results - Among the 1501 patients, 86% regularly received lipid-lowering drugs. LDL-C goals were achieved by 26% and 10% of patients with atherosclerotic cardiovascular disease (ASCVD) according to the 2016 and 2019 ESC/EAS dyslipidemia guidelines, respectively. High intensity lipid-lowering was administered more often in men than in women, in patients with ASCVD, at higher LDL-C and in patients with a genetic diagnosis of FH. - Conclusions - FH is under-treated in Germany compared to guideline recommendations. Male gender, genetic proof of FH, treatment by a specialist, and presence of ASCVD appear to be associated with increased treatment intensity. Achieving the LDL-C goals of the 2019 ESC/EAS dyslipidemia guidelines remains challenging if pre-treatment LDL-C is very high.